Existence of seven human IL-1R1 promoters - Qiming Li (Dove Medical Press, 2010)
Qiming Li, Hao Zhang, Qun Chen, Ning QuanDepartment of Oral Biology, Ohio State University, Columbus, OH, USAAbstract: Previous studies have reported the existence of three promoters for the human type I interleukin-1 receptor (hIL-1R1) gene. These promoters were discovered by identifying discrete transcription start sites (TSS) from limited human cell lines. In this study, we examined the TSSs of hIL-1R1 mRNA from 24 different tissues and identified several novel TSSs in hIL-1R1 that suggest the existence of seven hIL-1R1 promoters: three of them are the same as those reported previously and four are putative novel promoters. Using a promoter-reporter assay, we show here that these promoters can drive the transcription of the reporter gene. In addition, these promoters exhibit cell type specific expression patterns and they can be regulated by enhancer elements in a cell type specific manner. Only one of the promoters was found to be sensitive to the stimulation by glucocorticoids. Similar to our recent report on murine IL-1R1, two of the hIL-1R1 promoters appear to be the dominant promoters, one of which was published previously and the other is identified in the present study. We also found an internal promoter that drives the expression of IL-1R1 after the conventional translation start codon, suggesting that a truncated hIL-1R1 may be expressed by this promoter. These results provide additional information regarding the transcription of hIL-1R1.Keywords: type1 interleukin receptor, human IL-1R1 promoters, transcription start sites, reporter gene, stress hormones, acute phase proteins